47th Winter School on Wave and Quantum Acoustics XLVIth Winter School on Environmental Acoustics and Vibroacoustics Szczyrk, Poland, 26.02–01/02.03.2018 - Schools on Acoustic, Winter (Archives of Acoustics, 2018)
47th Winter School on Wave and Quantum Acoustics constitutes a platform for sharing the results and achievements obtained in different branches of physical acoustics. During the Conference Workshop on Acoustoelectronics and Workshop on Molecular Acoustics, Relaxation and Calorimetric Methods will be held. XLVth Jubilee Winter School on Environmental Acoustics and Vibroacoustics is the forum for all environmental and vibroacoustics fields. Particularly it concerns traffic noise, vibroacoustics of machines, room acoustics, building acoustics, noise protection and similar problems.